Catalytically Competent Fluorinated Barnase Variants - Langhans, Alexander; Krummhaar, Michael; Roth, Christian; Koksch, Beate (Synlett, 2024)
Proteins play critical roles in all living organisms, and their properties and functions result directly from their primary sequences. Fluorine, though seldom found in natural organic compounds, has been shown to impart desirable properties to small molecules and proteins alike. However, studies on the impact of this element in enzyme activity and protein–protein interaction are largely absent from the literature. Here we present a microwave-assisted SPPS method for the total synthesis of site-specifically fluorinated barnase variants, as well as characterization of their folding and activity. CD spectroscopy and fluorescence-based activity assays show that the fluorinated amino acids are generally not perturbative of the protein structure and that enzyme activity, albeit reduced, is retained in all variants.
Keywords: protein synthesis; fluorinated amino acids; enzyme activity